2010
DOI: 10.1007/s11920-010-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Health Anxiety: Current Perspectives and Future Directions

Abstract: Health anxiety is a ubiquitous experience that arises when bodily sensations or changes are believed to be indicative of a serious disease. Severe expressions of health anxiety are most often classified as hypochondriasis in the current DSM-IV-TR; however, various alternative classification schemas have been proposed for the DSM-V. Regardless of classification, severe health anxiety has significant negative impacts on well-being, social and occupational functioning, and health care resource utilization. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
141
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(163 citation statements)
references
References 37 publications
5
141
0
4
Order By: Relevance
“…In contrast, general illness worries and hypochondrical beliefs were rarer, suggesting these cognitions may specifically be an expression of significant HA. Illness worry may be related to an underlying medical condition (Asmundson et al 2010). However, chronic physical conditions were not found to account for the expressed level of concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, general illness worries and hypochondrical beliefs were rarer, suggesting these cognitions may specifically be an expression of significant HA. Illness worry may be related to an underlying medical condition (Asmundson et al 2010). However, chronic physical conditions were not found to account for the expressed level of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Health anxiety (HA) is a broad diagnostic construct encompassing excessive health and illness worries that extend from mild to severe forms with ICD-10-and the former DSM-IV-defined 'hypochondriasis' at the extreme clinical endpoint (Asmundson et al 2010;Creed and Barsky 2004). Severe HA is characterized by core cognitive, somatic and behavioral features (Asmundson et al 2010; Barsky et al 2001;Fink et al 2004;Rachman 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that engaging in frequent checking behaviors increases awareness of and preoccupation with bodily sensations and symptoms and perpetuates health-related fears, thereby exacerbating health anxiety (Abramowitz & Moore, 2007;Asmundson, Abramowitz, Richter, & Whedon, 2010;Salkovskis & Warwick, 1986. Thus it is possible that seeking health information online had a detrimental impact on participants with higher levels of health anxiety due to the increased frequency with which they engaged in this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…When thus clinically defined, it does not capture less severe forms of health anxiety that is dimensionally distributed in community and clinical settings (Asmundson, Abramowitz, Richter, & Whedon, 2010;Ferguson, 2009). Community-based studies indicated that as many as 10% of people exhibited health anxiety or the conviction of a serious illness, as measured by item 64 of the Screening for Somatoform Symptoms (SOMS) which measures the core feature of hypochondriasis (Rief, Hessel, & Braehler, 2001).…”
mentioning
confidence: 99%